Bone Formation from Porcine Dental Germ Stem Cells on Surface Modified Polybutylene Succinate Scaffolds - Nergis Abay; Gorke Gurel Pekozer; Mustafa Ramazanoglu; Gamze Torun Kose (Stem Cells International)
Designing and providing a scaffold are very important for the cells in tissue engineering. Polybutylene succinate (PBS) has high potential as a scaffold for bone regeneration due to its capacity in cell proliferation and differentiation. Also, stem cells from 3rd molar tooth germs were favoured in this study due to their developmentally and replicatively immature nature. In this study, porcine dental germ stem cells (pDGSCs) seeded PBS scaffolds were used to investigate the effects of surface modification with fibronectin or laminin on these scaffolds to improve cell attachment, proliferation, and osteogenic differentiation for tissue engineering applications. The osteogenic potentials of pDGSCs on these modified and unmodified foams were examined to heal bone defects and the effects of fibronectin or laminin modified PBS scaffolds on pDGSC differentiation into bone were compared for the first time. For this study, MTS assay was used to assess the cytotoxic effects of modified and unmodified surfaces. For the characterization of pDGSCs, flow cytometry analysis was carried out. Besides, alkaline phosphatase (ALP) assay, von Kossa staining, real-time PCR, CM-Dil, and immunostaining were applied to analyze osteogenic potentials of pDGSCs. The results of these studies demonstrated that pDGSCs were differentiated into osteogenic cells on fibronectin modified PBS foams better than those on unmodified and laminin modified PBS foams.